The Role of Tumor Stem Cell Exosomes in Cancer Invasion and Metastasis - Liu, Kun; Gao, Xin; Kang, Baoqiang; Liu, Yunpeng; Wang, Dingding; Wang, Yi (Frontiers in Oncology, 2022)
Exosomes are lipid membrane bilayer-encapsulated vesicles secreted by cells into the extracellular space. They carry abundant inclusions (such as nucleic acids, proteins, and lipids) that play pivotal roles in intercellular communication. Tumor stem cells are capable of self-renewal and are crucial for survival, proliferation, drug resistance, metastasis, and recurrence of tumors. The miRNAs in exosomes have various functions, such as participating in inflammatory response, cell migration, proliferation, apoptosis, autophagy, and epithelial-mesenchymal transition. Tumor stem cells secrete exosomes that act as important messengers involved in various tumor processes and several studies provide increasing evidence supporting the importance of these exosomes in tumor recurrence and metastasis. This review primarily focuses on the production and secretion of exosomes from tumors and tumor stem cells and their effects on cancer progression. Cancer stem cancer derived exosome play an important massager in the tumor microenvironment. It also emphasizes on the study of tumor stem cell exosomes in the light of cancer metastasis and recurrence aiming to provide valuable insights and novel perspectives, which could be beneficial for developing effective diagnostic and treatment strategies.